MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MODEL PRATAMA PADA MUATAN MATEMATIKA KELAS IV SDN SUNGAI MIAI 1 BANJARMASIN - Apriliani, Rosa Fitra; Prastitasari, Herti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low activity and learning outcomes in mathematics are due to the lecture-based learning method, which prevents students from interpreting learning problems. The solution is to use the PRATAMA model. This study aims to describe teacher activities and analyze the increase in student activity and learning outcomes. A qualitative research study of the type Classroom Action Research was conducted with four meetings. The subjects of the study were fourth-grade students at Sungai Miai 1 Elementary School in Banjarmasin, totaling 12 students in the 2024/2025 school year. Qualitative data was obtained through observations of teacher and student activities. Quantitative data was obtained through classical percentages of activity and student learning outcomes obtained from group and individual tests. Data analysis took the form of descriptions, tables, and graphs. The results showed that teacher activity increased from a score of 29 to a score of 41, meeting the "Very Active" criteria. Student activity increased from 25% to 83%, meeting the "Almost All Students are Very Active" criteria. This increase impacted student learning outcomes in the affective, cognitive, and psychomotor domains. Based on these results, using the PRATAMA model can improve student activity and learning outcomes. Teachers and other researchers can use this research as a reference for learning models that improve student learning activities and outcomes.